Investigating the role of oxidative stress in apoptosis induced by a sulphamoylated estradiol analogue in breast cell lines - Visagie, M.H. (Michelle Helen) (University of Pretoria, 2023)
Dissertation (MSc (Physiology))--University of Pretoria, 2020.